Influence of Conventional Shot Peening and Micro-Particle Peening Processes on the Surface Properties of 42CrMo Steel - HUANG Huaiyu, ZHANG Fulin, WANG Guanghong, LI Xinshuo, QIAN Qinlang, ZOU Wei, CAO Yufan, LIU Qi, CHEN Yongzhen, CHENG Zhen (Cailiao Baohu)
To investigate the effects of conventional shot peening and micro-particle shot peening on the surface properties of 42CrMo steel，ABAQUS software was employed to identify the primary and secondary influencing factors of these two processes on material surface roughness and the depth of the residual stress layer through orthogonal experiments.Based on the analysis results of the orthogonal experiments，practical experiments were conducted for validation.Considering the characteristics of micro-particle shot peening and conventional shot peening，a single-factor study of the shot peening coverage rate was carried out to examine the impact of these two processes on the residual stress，surface roughness and equivalent plastic strain of 42CrMo steel.Results showed that under the same coverage rate condition，micro-particle shot peening yielded higher residual compressive stress，lower surface roughness and higher equivalent plastic strain compared to conventional shot peening，accompanied by a slightly shallower strengthening layer.The increase in residual compressive stress contributed to improving wear resistance and fatigue performance of the material，while the lower surface roughness contributed to restraining crack initiation.Higher equivalent plastic strain could further refine grains and promote the generation of residual compressive stress.These advantages suggested the broad prospects of micro-particle shot peening in the surface strengthening of mechanical components.